Circular RNA PARG adjusts miR-140-3p to influence progression in sepsis: PARG adjusts miR-140-3p in sepsis - Zheng, Hongyi; Liu, Xianghong; Peng, Jinliang; Zhou, Yuming; Cheng, Hui; Xue, Zhengbiao; Wu, Chaoyu (Cellular and Molecular Biology, 2023)
Sepsis has been characterized as a frequent medical problem with high mortality and severe complication medical problem in the intensive care unit (ICU). Here, qRT-PCR was used to examine circRNA PARG expression levels in patients with sepsis and in human pulmonary microvascular endothelial cells (HPMEC). Lipopolysaccharide (LPS)-simulated HPMEC were hybridized using RNA-Fluorescence in situ hybridization to confirm the location of circRNA PARG and miR-140-3p. The biological role of downregulated circRNA PARGin cellular proliferation, apoptosis, and inflammatory and apoptosis responses was evaluated. performed A dual-luciferase reporter assay was performed to determine the relationship between the circRNA PARG with miR-140-3p. In this study,circRNA PARG aberrant expression was found, and the effects of circRNA PARG on lipopolysaccharide (LPS)-stimulated apoptosis of HPMEC cells were further investigated. Down-regulated circRNA PARG led to significant alleviation of LPS-simulated cell apoptosis via inhibition of inflammatory and apoptosis-related genes, while upregulated circRNA PARG exhibited the opposite effects. Further findings indicated that circRNA PARG positively modulated the relative level of miR-140-3p, which has been confirmed using the luciferase reporter assay. Upregulated circRNA PARG led to a reversal of LPS-simulated cells after transfection of miR-140-3p mimic. In general, a novel insight into understanding the important effects of circRNA PARG in sepsis is provided.